Establishment and characterization of a novel ovarian high-grade serous carcinoma cell line—IPO43 - Silva, Fernanda (2022)
Funding Information: We acknowledge to Unidade Investigação Patobiologia Molecular (UIPM) facilities and to Pathology Department of Instituto Português de Oncologia Francisco Gentil de Lisboa (IPOLFG). We acknowledge funding from the iNOVA4Health—UIDB/04462/2020 and UIDP/04462/2020, a program financially supported by Fundação para a Ciência e Tecnologia / Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES), through national funds”. Funding Information: The authors declare that the article was partially funded by iNOVA4Health—UIDB/04462/2020 and iNOVA4Health—UIDP/04462/2020.